Usulan Model Sistem Antrian pada Wisata Umbul Pelem dengan Pendekatan Teori Antrian dan Simulasi - Reza Arif Setiawan; Dwi Setiaji; Sri Widiyanti (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
The tourism sector in regional development, especially in Klaten, contributes significantly to income through various tourism potentials. The Klaten regional government is trying to increase this potential by developing facilities, providing comprehensive information, and increasing accessibility. The development of information and communication technology also encourages innovation in the tourism system. Apart from that, this study also highlights the phenomenon of queuing at public service facilities, such as in Umbul Pelem, which is caused by an imbalance between the number of customers and service capacity. With an average of 20 customers per day and a service time of 5-10 minutes per person, the system currently uses two service counters.